Fast detection method and device for release amount of nano-plastic and micro-plastic in plastic tableware
Patent Information
- Application Number
- CN202610642345.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-05-11
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-05-11
AI Technical Summary
[0004]本发明的目的在于提供塑料餐饮具中纳米塑料、微塑料释放量的快检方法及装置,以解决现有技术中检测周期长、操作繁琐、依赖大型实验室仪器、无法实现现场快检的不足
本发明将传统方法从迁移到出结果所需的数小时至数天缩短至约2小时(迁移30~40分钟+消解15~30分钟+染色10~30分钟+过滤10~20分钟+洗脱与检测5~10分钟),满足大批量样品快速筛查需求,需要说明的是,该时间为单样品检测流程时间,不含标准曲线建立(约需1天)和样品前处理(裁剪、清洗等,约10~20分钟)时间。
Smart Images

Figure CN122468683B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of food contact material safety testing technology, specifically to a rapid detection method and device for the release of nanoplastics and microplastics from plastic tableware. Background Technology
[0002] Microplastics (particle size less than 5 mm) and nanoplastics (particle size 1-1000 nm) have emerged as a new type of material contaminant, and their risk of release into food through plastic tableware is increasingly concerning. Studies have shown that during daily use, especially when microwaved or in contact with acidic or oily foods, plastic tableware can release large amounts of micro / nanoplastics into food. For example, microwave heating can cause the release of microplastics from takeout plastic containers to increase by more than 125 times, and oily food substrates can significantly promote the release of micro / nanoplastics and associated harmful chemicals from containers. A literature review published by the European Food Safety Authority (EFSA) in 2025 explicitly states that common food contact materials such as polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), polystyrene (PS), and polylactic acid (PLA) can release micro / nanoplastics during production, use, heating, or storage, with reported concentrations typically at 10⁻⁶. 2 Up to 10 6 The release behavior of micro / nanoparticles in food is a critical factor, and there is an urgent need for standardized detection methods and the development of reference standards. With the rapid application of new materials such as bio-based biodegradable plastics and nano-modified composite materials in food contact applications, the release behavior and detection and evaluation technologies for these new materials have become a key aspect of food safety evaluation. Therefore, it is imperative to establish a rapid detection method system adapted to the characteristics of these new materials.
[0003] Currently, the mainstream detection methods for micro / nanoplastics mainly include Fourier transform infrared spectroscopy (FTIR), laser Raman spectroscopy, pyrolysis-gas chromatography / mass spectrometry (Py-GC / MS), and nanoparticle tracking analysis (NTA). When applied to the detection of migration and release from tableware, the typical procedure is as follows: tableware samples are immersed in a food simulant solution for an extended period (2 hours to several days), followed by particle enrichment through filtration or centrifugation, and finally, microplastics are detected using microscopy / spectroscopy, while nanoplastics are detected using mass spectrometry or NTA. This type of solution has the following significant drawbacks: First, the detection cycle is long. From migration testing to instrumental analysis, the entire process usually takes several hours or even days. For example, the multi-stage dynamic release treatment scheme disclosed in Zhejiang University of Commerce patent CN121577868A requires low-temperature storage (24 hours), high-temperature heating (2 hours), and mechanical vibration (1 hour), followed by qualitative and quantitative analysis using scanning electron microscopy, micro-infrared spectroscopy, Py-GC / MS, and NTA, respectively. The total time exceeds 27 hours, which is difficult to meet the market supervision requirements for large-scale rapid sampling inspections of enterprise products, and even more so, it cannot meet the urgent need for rapid iterative evaluation methods in the research and development cycle of new materials. Second, the operation is cumbersome and the equipment cost is high. Existing solutions require the collaboration of multiple large instruments (such as scanning electron microscopes, micro-infrared spectroscopy, Py-GC / MS, NTA, etc.). The price of a single instrument is usually hundreds of thousands to millions of RMB, and they rely on professional technicians for operation and maintenance. While Zhejiang University of Technology's patent CN118883785A employs a two-step separation method using a 1μm glass fiber membrane and a 100kDa ultrafiltration centrifuge tube to separate micro / nanoplastics, it still requires final detection via Py-GC / MS, failing to reduce reliance on expensive pyrolysis-mass spectrometry equipment. Existing detection methods are ill-suited to the quality control requirements of rapid industrialization of new materials in terms of sensitivity, throughput, and equipment portability. Therefore, we propose a rapid detection method and device for the release of nanoplastics and microplastics from plastic tableware. It should be noted that international organizations such as ISO are currently developing microplastic detection standards. Our method has not yet undergone blind sample cross-validation with these ongoing standard methods, and its values cannot be directly traced to internationally recognized microplastic metrological benchmarks. Therefore, this method is positioned as a rapid screening tool for internal control and initial screening, rather than arbitration or compliance determination. This invention is particularly suitable for quality control screening during the R&D stage of new materials, rapid pre-evaluation of the food contact safety of new materials, and batch release inspection during the industrialization process of new materials. Summary of the Invention
[0004] The purpose of this invention is to provide a rapid detection method and device for the release of nanoplastics and microplastics in plastic tableware, so as to solve the shortcomings of the existing technology, such as long detection cycle, cumbersome operation, reliance on large laboratory instruments, and inability to achieve rapid on-site detection.
[0005] To achieve the above objectives, the present invention provides the following technical solution: a rapid detection method for the release of nanoplastics and microplastics from plastic tableware, comprising the following steps: S1. Migration Simulation: The plastic tableware sample to be tested is brought into contact with a food simulation liquid and accelerated migration is carried out at a temperature of 70~100℃ for 30~60 minutes to obtain a simulation liquid containing the migrated substances.
[0006] The food simulation liquid is selected from any one of the following according to the type of food that the tableware to be tested is expected to come into contact with: simulation liquid A for simulating contact with acidic foods, simulation liquid B for simulating contact with alcoholic foods, and simulation liquid C for simulating contact with oily foods. The design of this accelerated migration condition references the high-temperature short-time migration conditions (70°C / 2h or 100°C / 1h) in GB31604.1-2015 "General Rules for Migration Testing of Food Contact Materials and Articles". Through experimental verification, the migration time is shortened to 30-60 minutes within the range of 70-100°C. The migration amount of micro / nanoplastics deviates from the standard condition (70°C / 2h) by less than ±20%, which meets the accuracy requirements of rapid screening. However, this "equivalence" conclusion is currently only based on a single-point comparison experiment of 70°C / 2h and 95°C / 40min using PP lunch boxes and 95% ethanol as simulants. The universality for other temperature points, other materials and food simulants has not been fully verified, and it is not appropriate to directly extrapolate it to the entire 70-100°C range.
[0007] It should be noted that the accelerated migration conditions of this invention are not simply based on theoretical calculations of the Arrhenius equation, but rather optimized conditions verified through actual experiments. The rule that the reaction rate approximately doubles for every 10°C increase in temperature applies to homogeneous chemical reactions, while the desorption process of plastic particles involves interfacial physical interactions, making its temperature dependence more complex. Therefore, this invention determined the shortest effective migration time to be 30–60 minutes through comparative experiments; migration amounts below 30 minutes are insufficient, and the deviation from standard conditions exceeds an acceptable range.
[0008] S2, Nile Red Staining: Nile red staining solution is added to the simulated solution containing the emigrants obtained in step S1, and staining is carried out under light-protected conditions to label the emigrant micro / nanoplastics with fluorescent dye, resulting in a stained mixture.
[0009] Nile Red is a lipophilic fluorescent dye with an excitation wavelength of approximately 530 nm and an emission wavelength of approximately 620 nm (red fluorescence region). It produces a strong fluorescent signal after dissolving in a lipid medium and adsorbing onto the surface of plastics. However, Nile Red also exhibits co-staining with natural organic matter (such as lignin, humic acid, and proteins), which may lead to false positives. Therefore, this invention adds a hydrogen peroxide digestion step before staining to remove interference from natural organic matter that may be present in the food simulation solution. Specifically, 0.1–1.0 mL of 30% hydrogen peroxide solution is added to the cooled migration solution, and digestion is carried out at 60°C for 15–30 minutes, which effectively degrades most of the natural organic matter without affecting the integrity of the plastic particles. After digestion, the solution is cooled to room temperature before Nile Red staining.
[0010] Regarding the selectivity of Nile Red staining for microplastics, existing literature reports varying considerably. In pure plastic standard systems, the identification probability can reach over 95%; however, in real-world environmental samples, the false positive rate may significantly increase due to the presence of natural organic matter. This invention reduces the interference of natural organic matter to an acceptable level through a hydrogen peroxide digestion step.
[0011] This invention employs a method of first staining in the liquid phase and then gradient filtration, replacing the traditional method of first filtering and then staining the filter membrane. This method results in higher staining efficiency (the particles are fully dispersed in the solution, resulting in a large specific surface area), and the filtration step after staining naturally removes excess dye (excess dye is discharged with the filtrate), eliminating the need for a dedicated washing step.
[0012] S3. Multi-stage gradient filtration separation: The dyed mixture obtained in step S2 is passed through a multi-stage gradient filtration device to obtain filter media at each stage that retain the dyed plastic particles.
[0013] The multi-stage gradient filtration device includes at least two stages of filter media connected in series. The first stage of filter media traps micron-sized plastic particles, and the second stage of filter media traps nano-sized plastic particles. Each stage of filter media is independently removable. A single filtration operation can simultaneously trap micron-sized and nano-sized plastics, replacing the step-by-step operation mode of traditional methods that involves filtration followed by ultrafiltration and centrifugation.
[0014] It is important to note that the third-stage nanoplastic capture membrane uses an ultrafiltration membrane with a molecular weight cutoff of 50-150 kDa, and an equivalent pore size of approximately 5-20 nm. According to common knowledge in membrane separation, the actual pore size cutoff of a 100 kDa ultrafiltration membrane is approximately 5-10 nm (often cited as approximately 6 nm in the literature). Therefore, this ultrafiltration membrane may not be able to completely retain extremely small nanoplastic particles with a particle size range of 1-5 nm. This invention explicitly limits the detection range of nanoplastics to 5-1000 nm, rather than 1-1000 nm, to align with the actual retention performance of the ultrafiltration membrane. For the detection of nanoplastics in the 1-5 nm range, an ultrafiltration or nanofiltration membrane with a lower molecular weight cutoff (e.g., 10 kDa, equivalent pore size of approximately 2-3 nm) would be required, but this would significantly increase filtration time and operational complexity, making it unsuitable for rapid detection scenarios.
[0015] It is important to emphasize that there is no direct conversion between the molecular weight cutoff and particle size cutoff of the ultrafiltration membrane. The retention efficiency is significantly affected by factors such as particle morphology, surface charge, solution ionic strength, and membrane fouling. This method sets the detection limit for nanoplastics in a 100 kDa ultrafiltration membrane to approximately 5 nm, which is a simplified estimate based on ideal spherical particles. The actual usable limit should be calibrated through standard nanoparticle retention experiments. In the quantitative report of this method, the ultrafiltration membrane penetration loss (measured at approximately 8.5%) is not corrected; therefore, the nanoplastic quantity result implicitly represents a lower systemic level corresponding to the penetration ratio.
[0016] Furthermore, to avoid decreased retention efficiency due to membrane fouling, this invention requires pre-rinsing of each stage of the filter membrane with ultrapure water before use, maintaining an appropriate negative pressure (-30~-50 kPa) during filtration, and rinsing the membrane surface with a small amount of ultrapure water after filtration. For high-concentration samples or samples containing a large amount of colloidal matrix, it is recommended to increase the replacement frequency of the pre-filter membrane.
[0017] S4. Fluorescence Intensity Detection and Quantification: The Nile Red dye adsorbed by each stage of the filter media obtained in step S3 is eluted with elution solvent. The eluent is collected and its fluorescence intensity is measured at the excitation wavelength of 515~540nm and the emission wavelength of 600~650nm. The fluorescence intensity is substituted into the pre-established standard curve of micro / nanoplastics number concentration-fluorescence intensity to calculate the amount of nanoplastics and microplastics released by the tableware under the accelerated migration conditions.
[0018] Regarding the quantitative relationship between fluorescence intensity and particle number, this invention is based on the following principle: Under fixed particle size conditions, the amount of Nile Red adsorbed on the surface of plastic particles is positively correlated with the total surface area of the particles, while the total surface area is linearly related to the particle number (for spherical particles, total surface area = number of particles × ... After elution with organic solvents, all the dye was transferred into the solution, and the fluorescence intensity of the solution corresponded to the number of original particles.
[0019] However, this quantitative relationship has an important prerequisite: the particle size distribution of the particles in the sample should be consistent with the conditions for establishing the standard curve. The particle size distribution of nanoplastics released from actual tableware is quite wide (typically from tens to hundreds of nanometers), and the surface area / volume ratio of particles of different sizes varies greatly. For example, the specific surface area of a 100nm particle is 10 times that of a 1000nm particle; at the same mass concentration, the Nile Red adsorption capacity and fluorescence response of 100nm particles will be significantly higher than those of 1000nm particles.
[0020] To solve this problem, the present invention adopts the following strategies: (1) Establish standard curves for different particle size ranges (such as 100nm, 200nm, 500nm, and 1000nm); (2) In actual testing, select the corresponding standard curve according to the expected particle size distribution of the sample, or use a multi-particle-size mixed standard to establish a comprehensive standard curve; (3) In the data processing module, a particle size distribution correction algorithm is built in. Users can input the expected particle size distribution based on experience or pre-experiment results, and the system will automatically match the optimal standard curve.
[0021] It is important to emphasize that the quantitative result of this invention is the equivalent particle number based on the particle size of the standard, not an absolutely accurate particle number. For samples with unknown particle size distribution, it is recommended to pre-assess the particle size distribution using particle size analysis methods such as NTA or DLS to improve quantitative accuracy. Furthermore, the quantitative result of this method is affected by the varying staining efficiency of Nile Red on polymer type, particle morphology, and aging degree; differences in fluorescence response between different materials cannot be completely corrected by a single fixed relative fluorescence response coefficient. The relative coefficients for PP, PET, PLA, etc., provided below are only empirical values obtained under specified standard microsphere (2μm and 100nm PS microspheres) experimental conditions and are only used for approximate normalization of fluorescence efficiency differences between materials. When the particle size, morphology, and crystallinity of the detached particles in the actual sample differ significantly from those of the standard microspheres, this correction carries a significant risk of bias. The final reported value of this method is an approximate equivalent particle number and should not be considered as a precise quantification of absolute mass or particle number.
[0022] The core of the elution-fluorescence method lies in converting the fluorescence signal of stained particles into a photometric measurement signal in solution. High-throughput batch reading with a fluorescence spectrophotometer or ELISA reader replaces the traditional observation of individual particles under a fluorescence microscope and manual counting, greatly improving detection efficiency.
[0023] As a preferred technical solution, in step S1, the simulated solution A is an aqueous solution of acetic acid with a volume fraction of 1-5%, an accelerated migration temperature of 60-80℃, and a migration time of 30-40 minutes; the simulated solution B is an aqueous solution of ethanol with a volume fraction of 8-15%, an accelerated migration temperature of 50-70℃, and a migration time of 30-40 minutes; and the simulated solution C is an aqueous solution of ethanol with a volume fraction of 95% or refined olive oil, an accelerated migration temperature of 85-100℃, and a migration time of 30-40 minutes. The 95% ethanol aqueous solution, as a simulated solution for oily foods, complies with the requirements for alternative solvents for oily food simulants in GB31604.1-2015 and EU10 / 2011 standards. Its extraction capacity is superior to low-concentration ethanol, and it can more realistically simulate the release-promoting effect of oily foods on micro / nanoplastics in plastics.
[0024] As a preferred technical solution, the multi-stage gradient filtration device in step S3 includes the following components arranged in series along the liquid path: a first-stage pre-filtration membrane with a pore size of 5-20 μm, used to trap non-target large particulate impurities (such as food residue, dust, etc.); a second-stage microplastic capture membrane with a pore size of 0.8-1.2 μm, used to trap micron-sized plastic particles with a particle size ≥1 μm; and a third-stage nanoplastic capture membrane, which is an ultrafiltration membrane with a molecular weight of 50-150 kDa and an equivalent pore size of approximately 5-20 nm, used to trap nanoplastic particles with a particle size of 5-1000 nm. The first-stage pre-filtration membrane, the second-stage microplastic capture membrane, and the third-stage nanoplastic capture membrane are each encapsulated in a detachable filter unit, and each filter unit is sealed in series by a threaded connection or a snap-fit connection to form an integrated filter assembly. The three-tiered pore size setting corresponds to the particle size range of the target particles: 10 μm removes large particles to avoid clogging downstream membranes; 1 μm is the internationally recognized lower limit particle size for microplastics; and the pore size cutoff of a 100 kDa ultrafiltration membrane (equivalent pore size of approximately 6 nm) aligns with the lower detection limit for nanoplastics (5 nm), ensuring effective retention of micro- and nanoplastics across the entire particle size range above 5 nm. However, as mentioned above, this alignment is based on idealized assumptions, and in actual detection, retention near 5 nm may not be complete.
[0025] As a preferred technical solution, in step S2, the concentration of the Nile Red staining solution is 0.01~0.5 mg / mL, prepared using methanol or acetone as a solvent; the staining temperature is 15~35℃, and the staining time is 5~30 minutes. In step S4, the elution solvent is acetone, dimethyl sulfoxide, or a mixture thereof. Optimizing the staining solution concentration and staining time ensures sufficient staining of the particles while avoiding excessive free dye that could increase the background.
[0026] As a preferred technical solution, the standard curve of micro / nanoplastics number concentration-fluorescence intensity in step S4 is established as follows: using single-material microplastic and nanoplastic standards with known particle size and particle number concentration, nanoplastic standard solutions with particle sizes of 100nm, 200nm, 500nm, and 1000nm and microplastic standard solutions with particle sizes of 1μm, 2μm, and 5μm are prepared respectively, forming a series of standard solutions with gradient concentrations. Steps S1 to S4 are then performed sequentially on each standard solution to obtain the corresponding concentrations. Fluorescence intensity was measured, and number concentration-fluorescence intensity standard curves were established for each particle size range. In actual testing, the standard curve for the corresponding particle size range was selected for quantification based on the expected particle size distribution of the sample, or a comprehensive standard curve was established using mixed standards of multiple particle sizes. The single-material microplastic standards and nanoplastic standards were polystyrene (PS), polyethylene (PE), polypropylene (PP), polyethylene terephthalate (PET), or polylactic acid (PLA) microspheres / nanospheres, and the standards did not contain endogenous fluorescent markers to avoid interference with Nile Red fluorescence determination.
[0027] As a further preferred technical solution, the method also includes a polymer material correction step: for different plastic materials, establish a number concentration-fluorescence intensity standard curve to obtain the relative fluorescence response coefficient of each material relative to a selected reference material. In actual sample testing, if the material of the tableware is known (which can be obtained from the product label or through a routine FTIR analysis—the tableware material is usually determined during the production process), the fluorescence intensity measured in step S4 is corrected according to the corresponding relative fluorescence response coefficient. The relative fluorescence response coefficient is experimentally determined by the following method: taking the same particle number concentration (e.g., 1×10⁻⁶)... 6 Fluorescence intensity was measured using standard microspheres of different materials (PS, PE, PP, PET, PLA) with a density of 1 microsphere per mL, following steps S2-S4. The fluorescence intensity of PS was used as a baseline (1.0), and the relative coefficients for each material were calculated. At least six parallel measurements were performed for each material, and the average value was taken to calculate the relative standard deviation (RSD < 10%). Example data is as follows: with PS as the baseline material (1.0), the coefficients for PE are approximately 1.2, PET approximately 0.7, PP approximately 0.9, and PLA approximately 0.8. These coefficients are empirical correction values obtained from parallel measurements under specific particle size standard microsphere conditions (2 μm and 100 nm), and are only used to roughly normalize the differences in fluorescence efficiency between materials. When the particle size, morphology, crystallinity, and aging degree of the detached particles in the actual sample differ substantially from those of the standard microspheres, this correction carries a risk of bias. The number of particles obtained by this method is an approximate equivalent number and should not be considered as an accurate quantification of absolute mass or particle count. The above values are only examples; in actual applications, experimental measurements should be used as the standard, and periodic calibration is recommended.
[0028] As a preferred technical solution, the fluorescence intensity detection in step S4 is performed using a portable fluorescence spectrophotometer, a fluorescence microplate reader, or a multi-channel portable fluorescence detection device for batch reading; the technical parameters of the portable fluorescence detection device should meet the following requirements: excitation wavelength 530±10nm, emission wavelength 620±20nm, and detection limit not higher than 1×10⁻⁶. 4 Cells / mL (based on PS standard microspheres), linear range 1×10⁻⁶ 4 ~1×10 7 pcs / mL, linear correlation coefficient R 2 ≥0.99, intra-day and inter-day precision RSD <10%. It should be noted that the R value shown in the standard curve of this invention is... 2 Data with RSDs of ≥0.99 and approximately 1% at the high concentration end were obtained under strictly controlled laboratory conditions, using monodisperse standard microspheres and undergoing thorough ultrasonic dispersion and precise operation in the dark. In real-world sample matrices with more complex compositions, polydisperse particles, and a tendency to aggregate, the upper limit of the linear range and precision may deteriorate, and reproducibility between different laboratories requires further verification.
[0029] The present invention also provides an apparatus for implementing the above-described rapid detection method, comprising: A multi-stage gradient filtration assembly includes at least two filtration units that can be connected in series and sealed. Each filtration unit is encapsulated with a filtration membrane or ultrafiltration membrane of the required pore size for graded retention of dyed simulated liquid and separation of micron- and nano-sized plastic particles. The fluorescence detection module, including an excitation light source, a sample cell, and a photodetector, is used to detect the fluorescence intensity of the filter membrane eluent. The data processing and display module, electrically connected to the fluorescence detection module, is used to store standard curve data and calculate and display the release amount of micro / nanoplastics based on the measured fluorescence intensity. The data processing and display module has a built-in particle size distribution correction algorithm, which can automatically match the corresponding standard curve according to the expected particle size distribution information input by the user (such as mainly 100nm, wide distribution, etc.) and display the quantitative result of the equivalent particle number (based on XXnm standard). The displayed quantitative result does not correct for ultrafiltration membrane penetration loss, and the equivalent particle number is based on the standard microsphere particle size.
[0030] As a preferred technical solution, the multi-stage gradient filtration assembly includes: a first filtration unit filled with a pre-filtration membrane with a pore size of 5-20 μm; a second filtration unit filled with a microplastic capture membrane with a pore size of 0.8-1.2 μm; and a third filtration unit filled with an ultrafiltration membrane with a molecular weight cutoff of 50-150 kDa. Each filtration unit is sequentially and sealed via a threaded structure, forming a top-to-bottom flow pattern. A waste liquid collection container or a negative pressure receiving device can be connected to the bottom of the unit. A waste liquid collection bottle is provided at the bottom of the third filtration unit for collecting the filtrate that has permeated the ultrafiltration membrane. The retention efficiency of the ultrafiltration membrane can be evaluated by measuring the concentration of residual nanoplastics in the filtrate (e.g., using the NTA method). When the retention efficiency is below 90%, the ultrafiltration membrane should be replaced or the filtration conditions adjusted. The nanoplastic release amount reported by this method does not include particles that have permeated the ultrafiltration membrane. If it is necessary to assess the absolute total amount, the number of particles in the filtrate should be measured separately and corrected by summing.
[0031] The filtration device adopts a multi-stage sealed series structure to ensure that the filtration process is not contaminated by the external environment and effectively reduce blank value interference.
[0032] Compared with the prior art, the beneficial effects of the present invention are: This invention shortens the time required by traditional methods from several hours to several days to obtain results to approximately 2 hours (migration 30-40 minutes + digestion 15-30 minutes + staining 10-30 minutes + filtration 10-20 minutes + elution and detection 5-10 minutes), meeting the needs of rapid screening of large batches of samples. It should be noted that this time is the time for a single sample detection process, excluding the time for establishing a standard curve (approximately 1 day) and sample pretreatment (cutting, cleaning, etc., approximately 10-20 minutes).
[0033] This invention enables the separation and enrichment of micro / nanoplastics in one step through multi-stage gradient filtration. The elution-fluorescence method replaces microscopic counting or lysis chromatography analysis with photometric measurement. It supports multi-channel parallel batch reading of 96-well microplates and other instruments, greatly reducing the difficulty of operation.
[0034] This invention does not require expensive large-scale instruments such as scanning electron microscopes, micro-infrared spectrometers, Py-GC / MS, and NTA. The main detection equipment is only a fluorescence spectrophotometer or an enzyme-linked immunosorbent assay (ELISA) (the price is usually in the tens of thousands of RMB, which is less than one-tenth of the price of large-scale instrument combinations), and the cost of reagents consumed per detection is extremely low.
[0035] The migration conditions, dyeing parameters, filtration specifications, and quantitative methods of this invention are all defined by clear parameters. The parameter system is compatible with the national food contact material testing standard system, making it easy for the standards committee to adopt and form industry standards or national standards, thus filling the gap in the current standard system for rapid detection methods of micro / nanoplastics release.
[0036] The fluorescence detection module of this invention is compatible with portable fluorescence detection devices. The entire solution is easy to carry to market sampling sites or enterprise quality inspection laboratories, enabling rapid on-site screening without relying on a central laboratory. However, the quantitative accuracy of portable detection is slightly lower than that of laboratory fluorescence spectrophotometers, and it is recommended for initial screening. Positive samples can be sent to the laboratory for further confirmation. This method is positioned as a screening tool, and the results obtained are PS equivalent particle counts. Positive results or results near the threshold value must be confirmed by recognized chemical characterization methods such as Py-GC / MS and microspectroscopy before they can be used as a reference for compliance determination. Attached Figure Description
[0037] Figure 1 The standard curve of nanoscale plastic quantity concentration-fluorescence intensity was established for the PS microsphere standard in Example 1.
[0038] Figure 2 The standard curve of micron-scale plastic quantity concentration-fluorescence intensity was established for the PS microsphere standard in Example 1.
[0039] Figure 3 This is a correlation analysis diagram showing the results of the detection of multiple PP food container samples using the method of the present invention and the Py-GC / MS method.
[0040] Figure 4 This is a verification graph comparing the migration amount under accelerated migration conditions and standard conditions (70°C / 2h) in Example 5.
[0041] Figure 5 This is a comparison chart showing the digestion and removal effects of different natural organic substances in Example 6.
[0042] Figure 6 This is a comparison chart of the spiked recovery rates of PS standard microspheres in the humic acid-containing matrix in Example 6. Detailed Implementation
[0043] The present invention will be further described in detail below with reference to specific embodiments, comparative examples, and experimental examples. It should be understood that the specific embodiments described herein are only for explaining the invention and not for limiting the scope of protection of the invention. Parameter substitutions and process adjustments made by those skilled in the art based on the core concept of the invention without inventive effort are all within the scope of protection of the present invention. However, this method, as an equivalent particle number rapid screening method based on Nile Red fluorescent staining, has not yet undergone standardized verification across laboratories and methods, and the results obtained cannot be directly equated to the absolute particle number or mass concentration of internationally recognized methods (such as the ISO microplastic detection standard currently under development). Anyone making judgments based on this method should recognize this limitation.
[0044] The raw materials, reagents, and instruments used in the embodiments of this invention are all commercially available products in the art, obtained through commercial channels. Specifically: Nile Red dye was purchased from Sigma-Aldrich, with a purity ≥98%, CAS number 7385-67-3; non-fluorescently labeled polystyrene (PS) standard microspheres (particle sizes 100nm, 200nm, 500nm, 1000nm, 1μm, 2μm, 5μm, concentration 1.0×10⁻⁶) were used. 8 (1 / mL) was purchased from Zhongke Leiming Technology Co., Ltd. or Thermo Scientific; polyethylene (PE), polypropylene (PP), and polyethylene terephthalate (PET) standard microspheres were purchased from Zhongke Leiming Technology Co., Ltd.; polylactic acid (PLA) standard microspheres were purchased from Sigma-Aldrich; glass fiber membrane (Whatman GF / B, diameter 25 mm, nominal pore size 1.0 μm) was purchased from GE Healthcare; nylon filter membrane (diameter 25 mm, pore size 10 μm) was purchased from Merck Millipore; regenerated cellulose ultrafiltration membrane (Amico) was purchased. nUltra (diameter 25 mm, molecular weight cutoff 100 kDa, equivalent pore size approximately 6 nm) was purchased from Millipore; acetone (AR grade, purity ≥99.5%), methanol (AR grade, purity ≥99.5%), dimethyl sulfoxide (DMSO, AR grade, purity ≥99.5%), glacial acetic acid (AR grade, purity ≥99.5%), anhydrous ethanol (AR grade, purity ≥99.7%), and 30% hydrogen peroxide (AR grade) were all purchased from Sinopharm Chemical Reagent Co., Ltd.; refined olive oil was commercially available; ultrapure water was prepared using the Milli-Q system with a resistivity of 18.2 MΩ·cm.
[0045] The multi-stage gradient filtration device was self-assembled and consisted of three independent filtration units (each with an inner diameter of 25 mm), each filled with a nylon pre-filtration membrane, a glass fiber microplastic capture membrane, and a regenerated cellulose ultrafiltration membrane, respectively. Each unit was sealed in series via a PTFE threaded interface. Before use, each stage of the filtration membrane was pre-rinsed with 50 mL of ultrapure water to remove potential contaminants. Negative pressure was provided by a small diaphragm vacuum pump. Fluorescence detection was primarily performed using a Hitachi F-7100 fluorescence spectrophotometer (equipped with a 150W xenon lamp as the excitation source and an R928F photomultiplier tube detector) or a Thermo Scientific Varioskan LUX multifunctional microplate reader; portable detection and verification were performed using a self-made portable fluorescence detection module (530 nm LED excitation, 620 nm bandpass filter, SiPM detector). Py-GC / MS analysis was performed using a Frontier EGA / PY-3030D pyrolyzer coupled with an Agilent 7890B / 5977B GC-MS system. The pyrolysis temperature was 600℃, and the chromatographic column was an HP-5MS (30m × 0.25mm × 0.25μm). The mass spectrometry scan range was m / z 29–600. Nanoparticle tracking analysis (NTA) was performed using a Malvern NanoSight NS300 instrument for method comparison and particle size distribution validation. Example 1
[0046] Please see Figure 1-6 This embodiment provides a rapid detection method using a commercially available PP microwave-safe food container (approximately 500mL capacity, labeled as polypropylene, with a wall thickness of approximately 0.8mm) as the sample. Since the food container is intended to come into contact with hot, oily dishes, simulated solution C is used for detection. The specific steps are as follows: S1. Migration Simulation: Take the flat bottom and side walls of the PP lunch box and cut them into pieces with a total area of 2dm² using clean stainless steel scissors. 2 (Precisely measure two 10cm × 10cm sample pieces.) Wear powder-free nitrile gloves during the cutting process to avoid microplastic contamination. Place the sample pieces in a clean 250mL tall glass beaker, add 200mL of simulated solution C (95% volume fraction ethanol aqueous solution, prepared from anhydrous ethanol and ultrapure water at a volume ratio of 95:5) preheated to 95±2℃, and cover with a watch glass to reduce evaporation loss. Place the beaker in a constant temperature water bath and maintain the temperature at 95℃ for 40 minutes. Simultaneously, set up a blank control group—take a clean beaker of the same size, add only 200mL of simulated solution C, without adding the food container sample pieces, and treat under the same conditions. After migration, remove the food container sample pieces with clean stainless steel tweezers, rinse the surface of the sample pieces with a small amount of simulated solution (approximately 5mL), and combine the rinse solution with the migration solution. Transfer all the simulated solution to a clean 250mL Erlenmeyer flask to obtain a solution containing the effluent, and cool to room temperature.
[0047] S1a. Hydrogen peroxide digestion: Add 0.5 mL of 30% hydrogen peroxide solution to the cooled solution containing the effluent, and digest in a 60°C water bath for 20 minutes to remove interference from natural organic matter. Cool to room temperature after digestion.
[0048] S2. Nile Red Staining: Add 1.0 mL of 0.05 mg / mL Nile red-acetone staining solution (freshly prepared before use: dissolve 5.0 mg of Nile red powder in 100 mL of acetone) to the digested solution above, so that the final concentration of Nile red in the solution is approximately 0.25 μg / mL. After adding the solution, gently shake well, wrap the conical flask with aluminum foil to protect it from light, and let it stand at room temperature (25°C) for 10 minutes to obtain the stained mixture.
[0049] S3. Multi-stage gradient filtration separation: Connect the pre-assembled multi-stage gradient filtration device (from top to bottom: a first-stage 10μm nylon pre-filtration membrane unit, a second-stage 1.0μm glass fiber microplastic capture membrane unit, and a third-stage 100kDa regenerated cellulose nanoplastic capture membrane unit, with each unit sealed via a threaded connection) to a vacuum filtration flask, which is then connected to a diaphragm vacuum pump. Before use, pre-rinse each membrane with 50mL of ultrapure water. Slowly pour the stained mixture into the upper port of the filtration device, and turn on the vacuum pump to maintain a negative pressure of approximately -40kPa for filtration. After all liquid has passed through, continue aspiration for 2 minutes to remove as much residual liquid as possible from the surface of each membrane layer. Slowly rinse the surface of each membrane with 5mL of ultrapure water to remove residual food simulation liquid matrix. Turn off the vacuum pump, carefully disassemble each filtration unit, and use clean PTFE tweezers to remove the second-stage microplastic capture membrane and the third-stage nanoplastic capture membrane, placing them in clean petri dishes. Discard or retain the first-stage pre-filtration membrane for future reference. Collect the filtrate below the third-stage ultrafiltration membrane for retention efficiency evaluation.
[0050] S4. Fluorescence Intensity Detection and Quantification: The second-stage microplastic capture membrane and the third-stage nanoplastic capture membrane obtained in S3 were placed in two clean 10mL stoppered glass test tubes, respectively. 5mL of acetone was added to each tube as the elution solvent. After sealing, the tubes were placed on a vortex mixer and eluted at 2500rpm for 10 minutes. To verify the elution efficiency, the eluted membranes were eluted a second time (2mL of acetone was added, and the mixture was shaken for 5 minutes). The fluorescence intensity of the second eluent was measured. If the fluorescence intensity of the second eluent was 5% higher than that of the first, the elution time needed to be extended or the volume of the elution solvent increased. After standing for 1 minute, 2mL of the eluent from each tube was pipetted into a 10mm optical path quartz fluorescence cuvette, and the fluorescence intensity was measured using a fluorescence spectrophotometer. The measurement parameters were: excitation wavelength 530nm, emission wavelength 620nm, excitation slit width 5nm, emission slit width 10nm, photomultiplier tube voltage 700V, and scan speed 1200nm / min. The fluorescence intensity of the eluent from each stage of the blank control group was also measured. The fluorescence intensity of each stage of the sample's membrane eluent, after deducting the corresponding blank value, is taken as the net fluorescence intensity.
[0051] The net fluorescence intensity of the second-stage membrane eluent was substituted into a pre-established standard curve of the number concentration-fluorescence intensity of micron-sized plastic (2μm PS standard microspheres) (linear regression equation: y=0.0312x+8.7, R0). 2 =0.9948), the calculated microplastic release amount is 4.30 × 10⁻⁶. 5 pcs / dm 2 Substituting the net fluorescence intensity of the third-stage membrane eluent into the standard curve of the number concentration-fluorescence intensity of nanoscale plastics (100nm PS standard microspheres) (linear regression equation: y=0.0247x+12.5, R0) 2 =0.9962), the calculated release amount of nanoplastics is 8.70 × 10⁻⁶. 6 pcs / dm 2 The quantitative result is the equivalent particle number based on 2μm and 100nm PS standard microspheres. It has not been calibrated and extrapolated to correct for ultrafiltration membrane penetration loss (measured at approximately 8.5%). The actual total may be higher than this value by approximately 8.5%. The particle size distribution of nanoplastics in actual samples may differ from that of standards, and the quantitative result contains systematic errors related to particle size distribution.
[0052] The method for establishing the above standard curve is as follows: Take unlabeled PS standard microsphere stock solutions with particle sizes of 100 nm and 2 μm, and dilute them with 95% ethanol aqueous solution to prepare particle number concentrations of 0 and 1 × 10⁻⁶, respectively. 4 5×10 4 1×10 5 5×10 5 1×10 6 5×10 61×10 7 200 mL of a series of gradient standard solutions with particle number concentrations (particles / mL) were prepared. For each concentration point, the standard solution underwent hydrogen peroxide digestion, Nile red staining, multi-stage gradient filtration, elution, and fluorescence measurement following the same procedures as in Examples S1a-S4 of this embodiment. Each concentration point was measured six times. Linear regression using the least squares method was performed with particle number concentration (particles / mL) as the x-axis and net fluorescence intensity as the y-axis to establish number concentration-fluorescence intensity standard curves for both micrometer and nanometer scales. Simultaneously, standard curves for 100 nm, 200 nm, 500 nm, and 1000 nm nanoplastics and 1 μm, 2 μm, and 5 μm microplastics were established for particle size distribution correction.
[0053] For the PP food container material in this embodiment, the relative fluorescence response coefficient of PP relative to the reference material PS is known to be 0.9 (this coefficient was obtained through parallel measurements using PP standard microspheres using the same standard curve establishment procedure; the ratio of the slope of the PP standard curve to the slope of the PS standard curve is the relative response coefficient; 6 parallel measurements were performed, with an RSD of 4.2%). Therefore, the measured fluorescence intensity was first corrected by dividing by 0.9 before being substituted into the PS standard curve for calculation. This correction factor is an empirical value based on PP standard microspheres (2μm and 100nm), and its applicability to actual detached particles may be biased.
[0054] This embodiment takes approximately 70 minutes from sample cutting to obtaining the final result (including 20 minutes of digestion). Example 2
[0055] In this embodiment, a commercially available PET mineral water bottle (capacity 550mL, labeled material as PET, colorless and transparent, wall thickness approximately 0.3mm) was used as the test sample. This product is intended to come into contact with acidic beverages, and simulated solution A was selected for testing.
[0056] S1. Migration Simulation: Cut a PET bottle body into sections with a total area of 2 dm². 2 For the sample slide, add 200 mL of simulated solution A (3% volume fraction acetic acid aqueous solution, prepared by mixing glacial acetic acid and ultrapure water at a volume ratio of 3:97) preheated to 70±2℃, and incubate at a constant temperature of 70℃ for 40 minutes. A blank control is also provided. Collect all simulated solution after migration is complete.
[0057] S1a, Hydrogen peroxide digestion: Same as in Example 1.
[0058] S2. Nile Red Staining: After digestion of the solution containing the effluent, add 0.5 mL of Nile Red-Methanol Staining Solution with a concentration of 0.1 mg / mL (final concentration approximately 0.25 μg / mL), and incubate at 25°C in the dark for 5 minutes for staining.
[0059] S3, Multi-level gradient filtering separation: Same as Example 1.
[0060] S4. Fluorescence Intensity Detection and Quantification: Same as Example 1. Calculated after correction based on the relative fluorescence response coefficient of PET material relative to the PS reference (0.7, 6 parallel measurements, RSD=5.1%). Similarly, this coefficient is an empirical value based on PET standard microspheres.
[0061] After correction, the calculated amount of microplastics (particle size ≥ 1 μm) released from the PET mineral water bottle under simulated acidic beverage contact conditions is 1.10 × 10⁻⁶. 4 pcs / dm 2 The release amount of nanoplastics (particle size 5~1000nm) is 2.50×10⁻⁶. 5 pcs / dm 2 .
[0062] In this embodiment, the release amount of the PET bottle is significantly lower than that of the PP lunch box in Example 1. This is presumed to be related to the higher rigidity of the PET material, the fewer surface desorbed particles, and the lower migration temperature (70℃ vs 95℃). The result is consistent with the general understanding in the art of the difference in release behavior between the two materials in actual use. Example 3
[0063] In this embodiment, a commercially available PLA (polylactic acid) biodegradable cold drink cup (400mL capacity, labeled as PLA material, semi-transparent, wall thickness approximately 0.5mm) was used as the test sample. The intended food to be in contact with was an alcoholic beverage, and simulated solution B was selected for testing.
[0064] S1. Migration Simulation: Take a PLA cup and cut it into pieces with a total area of 2 dm. 2 The sample was mixed with 200 mL of simulated solution B (10% volume fraction ethanol aqueous solution) preheated to 60±2℃, and kept at a constant temperature in a 60℃ water bath for 40 minutes. A blank control was also set up.
[0065] S1a, Hydrogen peroxide digestion: Same as in Example 1.
[0066] S2. Nile Red Staining: Add 1.0 mL of Nile Red-acetone staining solution with a concentration of 0.05 mg / mL (final concentration approximately 0.25 μg / mL), and stain at 25°C in the dark for 15 minutes (the staining time may be extended appropriately to accommodate the possibility that the adsorption rate of Nile Red on PLA material may be slightly lower).
[0067] S3, Multi-level gradient filtering separation: Same as Example 1.
[0068] S4. Fluorescence Intensity Detection and Quantification: Same as in Example 1. The fluorescence response coefficient of PLA material relative to the PS reference (0.8, 6 parallel measurements, RSD = 6.3%) was calculated after correction. This coefficient is also an empirical value based on PLA standard microspheres.
[0069] After calibration and calculation, the microplastic release of this PLA cold drink cup under simulated alcoholic beverage contact conditions is 2.80 × 10⁻⁶. 4 pcs / dm 2 The amount of nanoplastics released was 6.10 × 10⁻⁶. 5 pcs / dm 2 . Example 4
[0070] This embodiment uses the same batch of commercially available PP microwave oven food containers as in Embodiment 1, but a portable fluorescence detection device is used instead of a laboratory fluorescence spectrophotometer in the detection scheme to verify the applicability of this method in portable rapid testing scenarios.
[0071] Steps S1 to S3 are exactly the same as in Example 1.
[0072] S4. Fluorescence Intensity Detection and Quantification: 200 μL of acetone eluent from the second and third stage membranes were added to the wells of a 96-well black ELISA plate (GreinerBio-One, Cat. No. 655076), with six replicates per sample. Batch readings were performed using a portable multi-functional fluorescence microplate reader (excitation wavelength 530 nm, emission wavelength 620 nm, bandwidth 20 nm). This portable device was verified by comparison with a laboratory fluorescence spectrophotometer, and the correlation coefficient R was [value missing]. 2 =0.987, in 1×10 4 ~1×10 7 The fluorescence signal showed good linearity within the range of cells / mL, with intra-day and inter-day precision RSDs of 4.5% and 7.2%, respectively. After reading, the fluorescence signal value (subtracting the average value of the blank replicates) was substituted into the standard curve for calculation.
[0073] The microplastic release was measured to be 4.10 × 10⁻⁶. 5 pcs / dm 2 The release amount of nanoplastics is 8.50 × 10⁻⁶. 6 pcs / dm 2 The results showed a deviation of less than 5% from those measured by the laboratory fluorescence spectrophotometer in Example 1 (microplastic deviation -4.7%, nanoplastic deviation -2.3%), indicating that the fluorescence quantification step of the present invention is compatible with portable fluorescence detection devices and meets the application requirements of on-site rapid testing scenarios. However, the lower limit of quantitation for portable detection (approximately 2 × 10⁻⁶) is limited. 4 The number of cells / mL is slightly higher than that of laboratory instruments (approximately 1 × 10⁻⁶). 4 (samples / mL), and for low concentration samples, it is recommended to retest using laboratory instruments.
[0074] Example 5: Accelerating the Verification of Migration Condition Equivalence To verify the equivalence of the accelerated migration conditions of this invention (70~100°C, 30~60 minutes) with the standard conditions of GB31604.1-2015 (70°C / 2h), the following comparative experiment was designed using PP lunch boxes as the test object: Take 6 sets of PP lunch box sample pieces from the same batch (2dm each) 2 Migration simulations were performed under the following conditions: Condition A (Standard Conditions): 70°C, 2 hours, 200 mL of 95% ethanol aqueous solution Condition B (Conditions of this invention): 95°C, 40 min, 200 mL of 95% ethanol aqueous solution Condition C (Validation Condition): 70°C, 40 min, 200 mL of 95% ethanol aqueous solution After migration, Nile red staining, multi-gradient filtration, and fluorescence quantification were performed according to steps S1a-S4 of Example 1. Each condition was measured in parallel 6 times.
[0075] result: Condition A (Standard): Microplastic release (4.15 ± 0.32) × 10 5 pcs / dm 2 The amount of nanoplastics released was (8.45±0.67)×10 6 pcs / dm 2 Condition B (Invention): Microplastic release amount (4.30±0.28)×10 5 pcs / dm 2 The amount of nanoplastics released was (8.70±0.58)×10 6 pcs / dm 2 Condition C (Verification): Microplastic release amount (3.62±0.41)×10 5 pcs / dm 2 The amount of nanoplastics released was (7.15±0.82)×10 6 pcs / dm 2 Compared to condition A, condition B shows a deviation of +3.6% for microplastics and +3.0% for nanoplastics, both within the acceptable range of ±20%. Compared to condition A, condition C shows a deviation of -12.8% for microplastics and -15.4% for nanoplastics, exceeding the acceptable range.
[0076] Conclusion: Validation showed that for this PP sample, no significant difference was observed in the release of micro / nanoplastics between 95°C / 40min and 70°C / 2h. The general applicability of this acceleration condition to other temperature points (such as 70°C / 30min, 100°C / 30min, etc.), other materials, and food simulants has not been verified and should not be directly generalized to the entire 70–100°C range. The acceleration conditions described in this method are only an experimental example based on the PP-95% ethanol system. Users who need to use it for other materials should verify the equivalence themselves. This validation data only supports the approximate equivalence of accelerated migration under this specific condition to standard conditions, meeting the needs of rapid screening.
[0077] Example 6: Selective Validation of the Method To verify the effectiveness of the hydrogen peroxide digestion step in removing interference from natural organic matter, the following experiment was designed: Take 200 mL each of ultrapure water (free of plastic particles), 3% acetic acid aqueous solution, 10% ethanol aqueous solution, and 95% ethanol aqueous solution, and add the following interfering substances respectively: Humic acid (simulating natural organic matter): 10 mg / L Protein (bovine serum albumin): 50 mg / L Lignin: 5 mg / L The above solutions were divided into two groups: Digestion group: Hydrogen peroxide digestion was carried out according to step S1a of the present invention (0.5 mL 30% H2O2, 60°C, 20 min). Undigested group: No digestion was performed; Nile Red staining was performed directly. Nile red staining, filtration, and fluorescence determination were performed according to steps S2-S4 of Example 1, and the results are shown in Table 1 below.
[0078] Table 1 The fluorescence signal of the undigested group was significantly higher than that of the blank (approximately 50±15), indicating a significant co-staining phenomenon between natural organic matter and Nile Red. After hydrogen peroxide digestion, the fluorescence signals of each interfering substance decreased to near the blank level, with a removal rate >93%.
[0079] At the same time, take PS standard microspheres of known concentration (100nm, 1×10⁻⁶) 6 Add (number / mL) to a solution containing humic acid (10 mg / L), and treat separately as a digestion group and an undigested group: Undigested group measured value: 1.85 × 10⁻⁶ 6 The number of positive samples per mL was 85% too high, indicating a high rate of false positives. Digestion group measured value: 1.02×10 6 cells / mL (deviation +2%, within acceptable range) Conclusion: The hydrogen peroxide digestion step can effectively remove the interference of natural organic matter on Nile Red staining and is a necessary step to ensure the selectivity of the method.
[0080] Comparative Example 1 The only difference between this comparative example and Example 1 is that the Nile Red staining step in step S2 is omitted. That is, the solution containing the effluent after migration is directly subjected to multi-stage gradient filtration in step S3 without staining, and in step S4, each stage of the filter membrane is directly eluted with acetone and its background fluorescence is measured. All other conditions are the same as in Example 1.
[0081] The test results showed that the fluorescence signals of the second and third stage membrane eluents at the excitation wavelength of 530 nm and the emission wavelength of 620 nm were not significantly different from those of the corresponding membrane eluents in the blank control group (the difference was <50 fluorescence units, which was within the instrument noise level), and therefore could not be effectively quantified.
[0082] This indicates that without Nile Red staining, the micro / nanoplastics themselves exhibit no characteristic fluorescence in the excitation / emission band and cannot be detected by fluorescence methods. Quantitative fluorescence detection of micro / nanoplastics requires labeling with a lipophilic fluorescent dye such as Nile Red.
[0083] Comparative Example 2 The difference between this comparative example and Example 1 is that single-stage filtration is used instead of multi-stage gradient filtration in step S3. Specifically, only a 1μm glass fiber membrane (GF / B) is used for a single filtration, without a 10μm pre-filtration membrane or a 100kDa ultrafiltration membrane. All residues on the 1μm membrane are collected for elution and fluorescence determination, and the filtrate is discarded without detection. All other conditions are the same as in Example 1.
[0084] The test results showed that the total particle release, calculated using the micron-level standard curve, was 5.12 × 10⁻⁶. 5 pcs / dm 2 The amount of microplastics obtained was significantly lower than that obtained by multi-stage gradient filtration in Example 1 (4.30 × 10⁻⁶). 5 pcs / dm 2 ) and nanoplastics (8.70×10 6 pcs / dm 2 ) and (approximately 9.13×10 6 pcs / dm 2 Analysis revealed that single-stage filtration only retained micron-sized particles ≥1μm, while a large number of nanoplastics (particle size <1μm) penetrated the 1μm filter membrane and entered the filtrate, resulting in a serious missed detection of approximately 94% of nanoplastics.
[0085] This indicates that traditional single-stage filtration schemes cannot effectively capture nanoplastic particles, and adding a nanocapture membrane (ultrafiltration membrane) stage is necessary and crucial for achieving accurate measurement of nanoplastics.
[0086] Comparative Example 3 This comparative example uses the multi-stage dynamic release + multi-instrument combination scheme disclosed in the embodiment of Zhejiang University of Commerce and Industry patent CN121577868A to test the PP microwave oven heating lunch boxes of the same batch as in Example 1.
[0087] Specifically as follows: Take 2dm 2 The food container sample was subjected to three simulated release processes: low-temperature storage (4℃, 24h, 200mL of 50% ethanol aqueous solution), high-temperature heating (100℃, 2h, replaced with 200mL of fresh 50% ethanol aqueous solution), and mechanical oscillation stress (reciprocating oscillation on a constant-temperature shaker at 100rpm for 1h). The release solutions from each stage were combined. After filtration through a 1μm glass fiber membrane, the morphology of the filter membrane was observed using scanning electron microscopy (SEM), and polymer chemical characterization and particle counting were performed using Micro-FTIR (at 1cm). 2 300 fields of view were randomly selected on the filter membrane area to count the number of positive particles with characteristic infrared absorption peaks of PP. The total number of microplastics was estimated based on the ratio of the field area to the total filter membrane area. The filtrate was analyzed for particle size distribution and particle concentration using NTA. The filtrate was also lyophilized and analyzed by Py-GC / MS. The filtrate was characterized by characteristic PP pyrolysis fragment ions (m / z=69, 83, etc.) and quantified using external standards based on the peak area of PP standard pyrolysis products.
[0088] Detection results: SEM+Micro-FTIR measured the release of microplastics (≥1μm) to be approximately 3.90×10⁻⁶. 5 pcs / dm 2 The NTA analysis showed that the main peak of the nanoplastic particle size distribution was located at 150 nm, and the particle number concentration was 4.20 × 10⁻⁶. 7 The number of cells / mL translates to a release amount of approximately 8.40 × 10⁻⁶. 6 pcs / dm 2 Py-GC / MS confirmed that the nanoplastic was made of PP. The total time for a single sample, from migration simulation to completion of all instrumental analyses, was approximately 28 hours.
[0089] Compared with Example 1: The amount of microplastics released by the method of the present invention (4.30 × 10⁻⁶) was significantly lower. 5 pcs / dm 2 The result deviated from that of Comparative Example 3 (microplastics) by approximately +10.3%; the release amount of nanoplastics (8.70 × 10⁻⁶) was... 6 pcs / dm 2 The deviation is approximately +3.6%. Compared to the total time of over 28 hours for Comparative Example 3, the method of this invention only takes about 70 minutes.
[0090] This indicates that, while maintaining good consistency with the results of the multi-stage release + multi-instrument analysis scheme of the prior art CN121577868A, the method of the present invention achieves a significant reduction in detection time (from >27 hours to approximately 70 minutes), thus significantly improving detection efficiency. The difference between the technical approach of the present invention and Comparative Example 3 is systematic: Comparative Example 3 obtains comprehensive particle size and chemical information through multi-stage release + individual characterization by multiple high-resolution instruments, but this is time-consuming and costly; the present invention achieves rapid quantification through single-stage standardized accelerated release + unified fluorescent dye labeling + batch photoelectric quantification, sacrificing the ability to characterize individual particles one by one, in exchange for a significant increase in speed and throughput, meeting the core requirements of rapid detection scenarios.
[0091] This comparison only uses PP food containers as an example, and the metrological traceability of the method in Comparative Example 3 was not compared with international microplastic standard references. Therefore, the absolute accuracy of neither method has been independently verified. The quantitative result of this invention is the equivalent particle number, and its accuracy is affected by the difference between the particle size of the standard and the particle size distribution of the actual sample. This is a reasonable compromise made by rapid detection methods in exchange for speed. For scenarios requiring precise particle size distribution and chemical qualitative information, it is recommended to use the multi-instrument combination scheme of Comparative Example 3 as a supplement.
[0092] Comparative Example 4 The difference between this comparative example and Example 1 is that step S4 uses the traditional Nile Red staining followed by fluorescence microscopy observation and counting method instead of the elution-fluorescence intensity method of the present invention.
[0093] Specifically: Steps S1 to S3 are the same as in Example 1. In S4, the filter membranes obtained in S3 are placed on a glass slide and sealed with a 50% glycerol aqueous solution. Observation is performed using an upright fluorescence microscope under green light excitation (excitation filter 530 / 40nm, dichroic mirror 565nm, emission filter 620 / 60nm). Under a 20x objective lens, 20 fields of view are randomly selected to capture red fluorescence images of the second-stage microplastic trapping membrane; under a 100x oil immersion lens, 30 fields of view are randomly selected to capture fluorescence images of the third-stage ultrafiltration membrane (the surface trapping material needs to be resuspended by ultrasound before being transferred to a coverslip for drying). The captured images are imported into ImageJ software for automatic thresholding and particle counting. The total number of particles on the entire filter membrane is calculated by magnifying the field area relative to the effective filtration area, and then converted into area release.
[0094] Test results: Microscopic counting method showed that the microplastic release amount was 3.80 × 10⁻⁶. 5 pcs / dm 2 The total release of nanoplastics is approximately 7.00 × 10⁻⁶. 6 pcs / dm 2The total time for single-sample microscopic counting is approximately 45 minutes (including sample preparation, photography, image processing, and manual parameter adjustment). Compared with the elution-fluorescence method results in Example 1, the deviation for microplastics is approximately -11.6%, and the deviation for nanoplastics is approximately -19.5%.
[0095] The reason for the large deviation in the counting of nanoplastics is presumed to be that particles with a diameter of less than 200 nm are still close to the optical diffraction limit (about 200 nm) under 100x oil immersion, and some extremely small nanoplastics have weak fluorescence signals, which are missed during image segmentation. However, the elution-fluorescence method of this invention is based on the integration of the total fluorescence signal of Nile Red in the solution, which is not limited by the optical diffraction limit. The fluorescence contribution of ultrafine nanoplastics is also included in the total signal, so it is closer to the true total release in terms of quantitative principle.
[0096] The comparative results show that although both the elution-fluorescence method of this invention and the existing fluorescence microscopy method are based on Nile red staining, they differ fundamentally in their quantitative mechanisms—the former is a total fluorescence signal integration method, while the latter is a single-particle counting method. The method of this invention avoids the optical diffraction limit faced by microscopic counting methods at the nanoscale, and simultaneously improves detection efficiency by approximately an order of magnitude (several minutes vs. 45 minutes) by replacing manual particle-by-particle counting with batch photoelectric reading, without requiring specialized optical and image processing experience for particle identification.
[0097] The following performance tests were performed on Examples 1-4 and Comparative Examples 1-4. The test items and test methods are as follows: Test Item 1: Standard Curve Establishment and Precision Evaluation Using unlabeled PS standard microspheres (100 nm and 2 μm in diameter) as standards, a series of standard solutions with gradient concentrations (0, 1 × 10⁻⁶, 1 × 10⁻⁶) were prepared according to the standard curve establishment method described in Example 1. 4 5×10 4 1×10 5 5×10 5 1×10 6 5×10 6 1×10 7 The particle number concentration (particles / mL) was digested with hydrogen peroxide, stained with Nile Red, subjected to multi-stage gradient filtration, elution, and fluorescence measurement, with each concentration point measured six times. A standard curve was established with particle number concentration (particles / mL) as the x-axis and net fluorescence intensity as the y-axis. The coefficient of variation (CV) of the six parallel measurements at each concentration point was calculated to evaluate the precision of the method.
[0098] Table 2 Standard curve data for nanoscale plastics (100nm PS standard microspheres) Linear regression equation: y = 0.0247x + 12.5, R0 2=0.9962.
[0099] The limits of detection (LOD) and quantitation (LOQ) are calculated as follows: LOD = 3.3 × σ / S, where σ is the standard deviation of fluorescence intensity of blank samples (n=20), and S is the slope of the standard curve. LOQ = 10 × σ / S The standard deviation of fluorescence intensity for the blank samples (n=20) was measured to be σ=18.5. Therefore: LOD=3.3×18.5 / 0.0247≈2.5×10 3 cells / mL LOQ = 10 × 18.5 / 0.0247 ≈ 7.5 × 10 3 cells / mL The detection limits and quantitation limits mentioned above are based on 100 nm PS standard microspheres. For particles of other sizes or materials, the detection limits may be different.
[0100] Table 3 Precision data of standard curves for micron-sized plastics (2μm PS standard microspheres) Linear regression equation: y = 0.0312x + 8.7, R² 2 = 0.9948.
[0101] LOD = 3.3 × 15.2 / 0.0312 ≈ 1.6×10 3 cells / mL LOQ = 10 × 15.2 / 0.0312 ≈ 4.9 × 10 3 cells / mL As can be seen from the data in Tables 1 and 2, the standard curves for nanometer and micrometer scales are at 1×10⁻⁶. 4 ~1×10 7 A good linear relationship was observed in the concentration range of 1 / mL (R0). 2 The coefficient of variation (CV) for each concentration point was >0.99%, and the CV for the high concentration range was less than 3%, indicating that the method of the present invention has satisfactory precision and a detection limit as low as 10. 3 The quantity is on the order of particles per mL.
[0102] However, it should be noted that the excellent linearity and precision data mentioned above were obtained under conditions of using monodisperse PS standard microspheres, ultrasonic dispersion, strict light protection, and completion by the same operator within a short period. In real-world complex samples, due to factors such as particle aggregation and matrix interference, the upper limit of the linear range may shift downwards, and the precision may deteriorate. Reproducibility between different laboratories has not been verified. Therefore, the above data should not be considered as performance indicators achievable under all conditions. For high-concentration samples (>1×10⁻⁶), 6 (particles / mL) should be monitored closely for internal filtration effects and fluorescence quenching caused by particle aggregation, and dilution verification is recommended.
[0103] Test Item 2: Spike Recovery Experiment The migration solution from the same batch of PP food containers as in Example 1 was used as the background solution (the background value was measured using the method in Example 1: approximately 2.75 × 10⁻⁶ micrometer-level background). 5 pcs / dm 2 The nanoscale background is approximately 8.12 × 10⁻⁶. 5 pcs / dm 2 (All values are the average of 6 parallel measurements). Add low concentrations (1×10⁻⁶) to the background solution. 5 (5×10) 5 (number / mL), high (2×10) 6 PS standard microspheres at three concentration levels (100 nm and 2 μm) were used as spiked samples, with six replicates prepared for each spike level. The determination was performed according to steps S1a-S4 of Example 1, and the spike recovery rate was calculated. The spike recovery rate calculation formula is: Recovery rate (%) = (Total measured amount - Background value) / Spiked amount × 100%.
[0104] Because there is a lack of commercially standardized reference materials for detached particles from real PP and other materials, this spiked recovery experiment used standard PS microspheres. It was only used to verify the overall recovery rate of known spherical particles in the Nile Red staining-filtration-elution experimental procedure, not the recovery rate of irregular particles from real PP. This experiment should more accurately be called "procedure recovery rate." For the quantitative accuracy of irregular particles in actual samples, indirect support is still needed through comparison with methods based on different principles, such as Py-GC / MS.
[0105] Table 4. Spike recovery test results (n=3) As shown in Table 4, the recoveries of the spiked micron and nanometer scales at the three spiking levels ranged from 93.0% to 115.6%, all within the acceptable range of 80% to 120% as generally accepted in the field. The relative standard deviation (RSD) ranged from 2.4% to 5.2%, indicating that the method of the present invention has good accuracy and repeatability.
[0106] Test Item 3: Method Selectivity Validation Following the method described in Example 6, the removal effect of the hydrogen peroxide digestion step on interference from natural organic matter was verified. The results showed that the removal rate of common natural organic matter such as humic acid, protein, and lignin after digestion was >93%, effectively avoiding false positives.
[0107] Test Item 4: Precision Verification of Actual Samples Take three different brands of tableware made of three different materials (PP lunch boxes, PET water bottles, and PLA cold drink cups) and perform parallel measurements (n=6) according to the methods in Examples 1-3 to calculate intra-day and inter-day precision.
[0108] result: PP food containers: Microplastics RSD = 5.2% (intraday), 7.8% (daytime); Nanoplastics RSD = 6.5% (intraday), 8.9% (daytime) PET water bottles: Microplastics RSD = 4.8% (intraday), 7.2% (interday); Nanoplastics RSD = 5.9% (intraday), 8.1% (interday) PLA cold drink cups: Microplastics RSD = 6.1% (daytime), 8.5% (daytime); Nanoplastics RSD = 7.2% (daytime), 9.3% (daytime) The above precision data reflects the complexity of actual samples (matrix differences, uneven particle size distribution, etc.). The RSD is slightly higher than that of the standard test, but it still meets the requirements for rapid screening.
[0109] Test Item 5: Verification of Ultrafiltration Membrane Retention Efficiency Take 100nm PS standard microsphere solution (1×10 6 200 mL of ultrafiltration solution (particles / mL) was subjected to multi-stage gradient filtration according to step S3 of Example 1. The filtrate below the third-stage ultrafiltration membrane was collected, and the residual particle concentration was determined by NTA.
[0110] Results: The concentration of residual particles in the filtrate was (8.5±2.1)×10⁻⁶. 4 Cells / mL, Retention efficiency = (1×10) 6 -8.5×10 4 ) / 1×10 6 ×100%=91.5%.
[0111] This retention efficiency is within an acceptable range (>90%), but indicates that approximately 8.5% of 100 nm particles still permeate the ultrafiltration membrane. For smaller particles (e.g., 50 nm), the retention efficiency may decrease further, which is an inherent limitation of ultrafiltration membrane separation. This method does not correct for this permeation loss in the final reported nanoplastic quantity, therefore the results implicitly underestimate the system by approximately 8.5%. To obtain the total nanoplastic quantity, the filtrate must be separately measured and summed.
[0112] Comparative analysis of comprehensive data from examples and comparative cases To visually demonstrate the core performance differences between the method of this invention and the comparative schemes, the key indicators are summarized as follows: Table 5 Comparison of key performance indicators between the examples and comparative examples. From the data in Table 5 and the comparative analysis of the examples and comparative examples, we can conclude that: 1) Comparative Example 1 demonstrates the necessity of the Nile Red staining step – without staining, no detectable fluorescence signal can be generated, which is the prerequisite for achieving quantitative fluorescence.
[0113] (2) Comparative Example 2 demonstrates the necessity of nanocapture membrane (100kDa ultrafiltration membrane) in multi-stage gradient filtration. Traditional single-stage 1μm filtration only traps micron-sized plastics, and a large number of nanoplastics penetrate the filter membrane (missed detection rate >94%). It is necessary to add an ultrafiltration membrane stage to achieve effective quantification of nanoplastics.
[0114] (3) Comparative Example 3 demonstrates that the method of the present invention has good consistency with the existing multi-stage release + multi-instrument analysis scheme (CN121577868A) in terms of detection results (microplastic deviation of about 10% and nanoplastic deviation of about 4%). However, the method of the present invention shortens the detection time from 28 hours to about 70 minutes, and improves efficiency by about 24 times. The quantitative result of the present invention is the equivalent particle number, and its accuracy is affected by the difference between the particle size of the standard and the particle size distribution of the actual sample. This is a reasonable compromise made by the rapid detection method in exchange for speed.
[0115] (4) Comparative Example 4 demonstrates the advantages of the elution-fluorescence method of the present invention over the traditional microscopic counting method after Nile Red staining: both are quantitative methods after Nile Red staining, but the elution-fluorescence method replaces single particle counting with total fluorescence signal integration, avoiding the diffraction limit limitation of optical microscope at the nanoscale (especially <200nm), while the detection efficiency is greatly improved (fluorescence reading only takes a few seconds to a few minutes, while microscopic counting requires about 45 minutes of manual operation) and no image analysis expertise is required.
[0116] (5) Example 5 demonstrates that for PP lunch boxes under 95% ethanol conditions, there is no significant difference between 95°C / 40min and standard conditions of 70°C / 2h. However, this conclusion is limited to this specific condition and cannot be simply extrapolated.
[0117] (6) Example 6 demonstrates that the hydrogen peroxide digestion step effectively removes interference from natural organic matter, ensuring the selectivity of the method.
[0118] In summary, the rapid detection method and device for nanoplastics and microplastics released from plastic tableware provided by this invention utilizes a standardized, accelerated migration simulation, natural organic matter digestion, Nile red fluorescent staining, multi-stage gradient filtration integrated separation, elution, and rapid fluorescence quantification technique. While ensuring the accuracy of the detection results is consistent with existing standard methods, it reduces the single-sample detection time from several hours to several days to approximately 70 minutes, significantly reducing operational complexity and equipment costs. It also possesses the capability to be adapted to portable fluorescent detection devices for on-site rapid detection, demonstrating significant technological advancement and broad industrial application prospects in the field of food contact material safety testing. It should be reiterated that this method is an internally developed rapid screening method based on PS equivalent particle number. The results are in user-defined units and have not undergone inter-laboratory or cross-method standardization validation. Therefore, it is not suitable for direct use as a basis for compliance judgment or health risk limits. Positive results must be confirmed by recognized chemical characterization methods (such as Py-GC / MS, microspectroscopy, etc.). This method is positioned as a primary screening tool for internal control and relative comparison.
[0119] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention. For example, the specific pore sizes of each stage of the filtration membrane can be adjusted within the range defined in the claims according to the segmented requirements of the target particle size (e.g., the pre-filtration membrane can be selected in the range of 5~20μm, the microplastic capture membrane can be selected in the range of 0.8~1.2μm, and the ultrafiltration membrane can be selected in the range of 50~150kDa, but the detection limit of nanoplastics is adjusted accordingly to the particle size corresponding to the actual pore size of the ultrafiltration membrane, such as approximately 5nm for a 100kDa ultrafiltration membrane); the Nile red staining concentration and staining time can be finely adjusted within the range defined in the claims according to the specific sample conditions; the specific ratio of the food simulation solution can be adjusted within the content range defined in the claims to meet the simulation requirements of different food types; the elution solvent can be an organic solvent with similar solubility, such as dimethyl sulfoxide or an acetone-dimethyl sulfoxide mixture; the connection method of the multi-stage gradient filtration device can be a snap-fit sealing connection instead of a threaded connection; the fluorescence detection device can be a fluorescence microplate reader or a portable multi-channel fluorescence detector with similar detection functions. It should be noted that the rapid detection method of this invention is positioned as a screening method, and the quantitative result is the equivalent particle number, suitable for rapid initial screening and relative comparison of large batches of samples. For positive samples or scenarios requiring precise absolute quantification, it is recommended to use standard methods such as NTA and Py-GC / MS for confirmatory analysis. Any modifications, equivalent substitutions, and improvements made within the spirit and principles of this invention should be included within the scope of protection of the claims of this invention. In particular, the correspondence between the molecular weight cutoff and pore size of the ultrafiltration membrane, the applicability of the relative fluorescence response coefficient, the boundary conditions of the standard curve performance, and the range of accelerated migration equivalence should all be based on the above limiting descriptions and should not be misinterpreted as absolute universal laws. The scope of protection of this invention is defined by the appended claims and their equivalents.
Claims
1. A rapid detection method for the release of nanoplastics and microplastics from plastic tableware, characterized in that, Includes the following steps: S1. Migration Simulation: The plastic tableware sample to be tested is brought into contact with a food simulation liquid and accelerated migration is carried out at a temperature of 70~100℃ for 30~60 minutes to obtain a simulation liquid containing the migrating substances. In step S1, the simulated solution A is an aqueous solution of acetic acid with a volume fraction of 1-5%, the accelerated migration temperature is 60-80℃, and the migration time is 30-40 minutes; the simulated solution B is an aqueous solution of ethanol with a volume fraction of 8-15%, the accelerated migration temperature is 50-70℃, and the migration time is 30-40 minutes; the simulated solution C is an aqueous solution of ethanol with a volume fraction of 95% or refined olive oil, the accelerated migration temperature is 85-100℃, and the migration time is 30-40 minutes. S2, Nile Red Staining: Nile red staining solution is added to the simulated solution containing the emigrants obtained in step S1, and staining is carried out under light-protected conditions to label the emigrant micro / nanoplastic particles with fluorescent dye, resulting in a stained mixture. S3. Multi-stage gradient filtration separation: The dyed mixture obtained in step S2 is passed through a multi-stage gradient filtration device to obtain filter media at each stage that retain the dyed plastic particles. S4. Fluorescence intensity detection and quantification: The Nile red dye adsorbed by each stage of the filter media obtained in step S3 is eluted with elution solvent. The eluent is collected and its fluorescence intensity is measured at the excitation wavelength of 515~540nm and the emission wavelength of 600~650nm. The fluorescence intensity is substituted into the pre-established standard curve of micro / nanoplastics number concentration-fluorescence intensity to calculate the amount of nanoplastics and microplastics released by the tableware under accelerated migration conditions. In step S1, the food simulation liquid is selected from any of the following according to the type of food that the tableware to be tested is expected to come into contact with: simulation liquid A for simulating contact with acidic food, simulation liquid B for simulating contact with alcoholic food, and simulation liquid C for simulating contact with oily food. In step S3, the multi-stage gradient filtration device includes at least two stages of filter media connected in series. The first stage filter media traps micron-sized plastic particles, and the second stage filter media traps nano-sized plastic particles. Each stage of filter media is independently removable, and the multi-stage gradient filtration device includes components arranged in series along the liquid path direction. The first-stage pre-filtration membrane has a pore size of 5~20μm and is used to remove non-target large particulate impurities. The second-stage microplastic capture membrane has a pore size of 0.8~1.2μm and is used to trap micron-sized plastic particles. The third-stage nanoplastic capture membrane is an ultrafiltration membrane with a molecular weight cutoff of 50~150kDa and an equivalent pore size of 5~20nm, used to trap nanoplastic particles with a particle size of 5~1000nm. In step S2, the concentration of the Nile Red staining solution is 0.01~0.5 mg / mL, prepared with methanol or acetone as solvent; the staining temperature is 15~35℃, and the staining time is 5~30 minutes; the elution solvent is acetone, dimethyl sulfoxide, or a mixture thereof; before staining, 0.1~1.0 mL of 30% hydrogen peroxide solution is added to the simulation solution, and the solution is digested at 60℃ for 15~30 minutes to remove interference from natural organic matter, and then Nile Red staining is performed after cooling to room temperature; In step S4, the standard curve of the number concentration-fluorescence intensity of micro / nanoplastics is established as follows: using single-material microplastic and nanoplastic standards with known particle size and particle number concentration, nanoplastic standard solutions with particle sizes of 100nm, 200nm, 500nm, and 1000nm and microplastic standard solutions with particle sizes of 1μm, 2μm, and 5μm are prepared respectively, and a series of standard solutions with gradient concentrations are prepared. The operations of steps S1 to S4 are performed sequentially on each standard solution to obtain the fluorescence intensity corresponding to each concentration, and the number concentration-fluorescence intensity standard curves for each particle size range are established respectively. In actual detection, the standard curve of the corresponding particle size range is selected for quantification according to the expected particle size distribution of the sample, or a comprehensive standard curve is established using mixed standards of multiple particle sizes. The single-material microplastic and nanoplastic standards are polystyrene, polyethylene, polypropylene, polyethylene terephthalate, or polylactic acid microspheres / nanospheres, and do not contain endogenous fluorescent markers.
2. The rapid detection method for the release of nanoplastics and microplastics in plastic tableware according to claim 1, characterized in that: The first-stage pre-filtration membrane, the second-stage microplastic capture membrane, and the third-stage nanoplastic capture membrane are each encapsulated in a detachable filtration unit. Each filtration unit is sealed in series by threaded or snap-fit connections to form an integrated filtration assembly. This allows particles in the simulated liquid to be graded and trapped on different membrane layers according to their particle size in a single filtration operation. Each filtration unit needs to be pre-washed with ultrapure water before use to remove potential contaminants. During the filtration process, a negative pressure of -30 to -50 kPa is maintained. After filtration, the surface of each membrane is rinsed with a small amount of ultrapure water to remove residual food simulated liquid matrix.
3. The rapid detection method for the release of nanoplastics and microplastics in plastic tableware according to claim 1, characterized in that: It also includes a polymer material calibration step: for different plastic materials, establish a number concentration-fluorescence intensity standard curve to obtain the relative fluorescence response coefficient of each material relative to the selected reference material. In actual sample testing, if the material of the tableware is known, the fluorescence intensity measured in step S4 is corrected according to the corresponding relative fluorescence response coefficient. The relative fluorescence response coefficient is determined by the following method: take standard microspheres of different materials with the same particle number concentration, measure the fluorescence intensity according to steps S2 to S4, use the fluorescence intensity of polystyrene as the reference, calculate the relative coefficient of each material, measure each material in parallel at least 6 times, take the average value and calculate the relative standard deviation.
4. The rapid detection method for the release of nanoplastics and microplastics in plastic tableware according to claim 1, characterized in that: In step S4, the fluorescence intensity detection is performed in batches using a portable fluorescence spectrophotometer, a fluorescence microplate reader, or a multi-channel portable fluorescence detection device; the detection limit of the portable fluorescence detection device should not be higher than 1×10⁻⁶. 4 The linear correlation coefficient R² ≥ 0.99 was achieved, and the intra-day and inter-day precision RSD < 10%.
5. An apparatus for implementing a rapid detection method for the release of nanoplastics and microplastics from plastic tableware according to any one of claims 1 to 4, characterized in that: include: A multi-stage gradient filtration assembly includes at least two filtration units that can be connected in series and sealed. Each filtration unit is encapsulated with a filtration membrane or ultrafiltration membrane of the required pore size for graded retention of dyed simulated liquid and separation of micron- and nano-sized plastic particles. The fluorescence detection module, including an excitation light source, a sample cell, and a photodetector, is used to detect the fluorescence intensity of the filter membrane eluent. The data processing and display module is electrically connected to the fluorescence detection module. It is used to store standard curve data and calculate and display the release amount of micro / nanoplastics based on the measured fluorescence intensity. The data processing and display module has a built-in particle size distribution correction algorithm, which can automatically match the corresponding standard curve according to the expected particle size distribution information input by the user. The multi-level gradient filtering component includes: The first filtration unit is filled with a pre-filtration membrane with a pore size of 5~20μm; The second filtration unit is filled with a microplastic capture membrane with a pore size of 0.8~1.2μm; The third filtration unit is filled with an ultrafiltration membrane with a molecular weight cutoff of 50~150kDa; Each filtration unit is sequentially sealed and connected by a threaded structure, forming an overall flow direction from top to bottom. The bottom can be connected to a waste liquid collection container or a negative pressure receiving device. The bottom of the third filtration unit is equipped with a waste liquid collection bottle to collect the filtrate that has penetrated the ultrafiltration membrane in order to evaluate the retention efficiency of the nanoplastics. The actual retention performance of the ultrafiltration membrane in the third filtration unit is affected by the particle morphology, surface properties and solution conditions, and needs to be calibrated by standard nanoparticle retention experiments.
Citation Information
Patent Citations
Method for simulating and detecting micro / nano plastic released by food contact plastic product
CN121577868A
Thermal cycle method for preparing fluorescent dyed micro-plastics and concentration analysis method
CN112730368A
Microplastic fluorescent staining quantitative detection method based on Nile red staining agent
CN115753720A